Seismic Stability Time-Frequency Analysis Method of Reinforced Retaining Wall. (23rd June 2015) - Changwei, Yang; Shixian, Zhang; Jianjing, Zhang; Junwei, Bi
Abstract : The first-order differential equation of the seismic active earth pressure is established by horizontal slices analysis method, based on the elastic wave theory, with the summarized dynamic analysis model of the reinforced retaining wall and the plane of fracture assumed as linear type. And then this paper proposes a time-frequency analysis method for the internal antiseismic stability analysis on the retaining wall. The reasonability of this method is verified by the results from other methods, for example, rule. The internal frictional angle of filling earth, the seismic intensity, and the frequency of the input earthquake wave have a predominant effect on the needed total tensile force of the lacing wires, which shows that (1) the needed total tensile force of the lacing wires goes up with the increase of the PGA and the internal frictional angle; (2) the needed total tensile force of the expandability lacing wires is bigger than that of the nonexpandability lacing wires; (3) the needed total tensile force of lacing wires is saddle distributed and the force achieves maximum value when the frequency of input wave equals the natural frequency of reinforced retaining wall. Besides, if the reinforced retaining wall is designed in compliance with the rules, the emergency capacity of reinforced retaining wall is reduced. At last, this paper not only takes into account the effect of three factors of the seismic wave (PGA, frequency, and duration) on the internal antiseismic stability analysis of reinforced retaining wall but also provides some valuable references for the time-frequency seismic design of other retaining structures.